Eugenol-grafted aliphatic polyesters: Towards inherently antimicrobial PLA-based materials exploiting OCAs chemistry. (May 2019) - Gazzotti, Stefano; Todisco, Simona Alessandra; Picozzi, Claudia; Ortenzi, Marco Aldo; Farina, Hermes; Lesma, Giordano; Silvani, Alessandra
Graphical abstract: Highlights: The synthesis of highly functionalized polyester-based materials through OCAs polymerization is presented. Eugenol-bearing OCA monomer was synthesized and polymerized. Copolymers with L-Lactic acid derived OCA were successfully obtained. Homopolymerization product shows antimicrobial activity. Abstract: PLA-based materials with eugenol moieties covalently bonded to the macromolecular chains were synthesized for potential application in bioactive food packaging. The synthetic strategy relies on the exploitation of O-Carboxyanhydrides (OCAs) as versatile and easily modifiable monomers. More precisely, eugenol-bearing L-malic acid-derived OCA (L-MalOCA) was synthesized and used as monomer, in homo- and co-polymerization reactions. In the latter case, two different ratios of functionalized L-MalOCA were employed, with respect to the standard L-lactic acid-derived OCA (L-LacOCA) monomer. Homopolymer and copolymers were fully characterized and their thermal properties were investigated, highlighting the effect on the final polymer of varying the concentration of the L-MalOCA-derived monomer. A moderate antimicrobial activity was detected for the eugenol-rich L-MalOCA-derived homopolymerization product, making it promising for developments in the field of bioactive and biodegradable PLA-based materials.